Three-Dimensional Landslide Model For Predicting Affected Area With Particle Flow Simulation - Nobaew, Banphot (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2010)
- Landslides are a serious natural disaster in many countries around the world especially in highland areas during the rainy season. Therefore an early warning system which can predict the possibility of landslide in hazard areas is seriously required to prevent damage to life and assets. Three-dimensional models are also needed to simulate landslide areas for prediction of the overall effects. This paper describes a new three-dimensional landslide model by applying a methodology consisting of image processing, use of global positioning system, and risk factor interaction on programming. A landslide model is built by contouring the surveyed sites. In addition, a 3D Studio MAX script is employed based on existing risk factors to simulate the flow of land particles during the occurrence of a landslide. Based on observations of the landslide site, the proposed method shows acceptable accuracy on both the probability of landslide incident and its effects.